Who comes in second? The race against sulfonylureas and DPP4s as add‐on therapy. Issue 10 (October 2017) - Lyon, Corey
Abstract : N/A: Ou SM, Shih CJ, Chao PW, Chu H, Kuo SC, Lee YJ, et al. Effects on clinical outcomes of adding dipeptidyl peptidase‐4 inhibitors versus sulfonylureas to metformin therapy in patients with type 2 diabetes mellitus. Ann Intern Med . 2015; 163(9):663–672.